Development of a Valid Instrument for Assessing University Student Character Strengths in Pakistani Academic Setting - Green, Zane Asher (2024)
This research comprised two studies. The purpose of Study 1 was to develop and evaluate the psychometric properties of the Character Strengths Scale for University Students (CSSUS)—a domain-specific measure reflecting the use of character strengths in the academic setting. The purpose of Study 2 was to test the application of the CSSUS. The study population comprised students from 18 undergraduate programs under the disciplines of social sciences, management sciences, and computer sciences at 22 universities of Islamabad. A random name picker on the Internet randomly identified three sets of different undergraduate programs from the 18. Astratified random sample was drawn from each set. Derived from best practices, the item development of the CSSUS was based on four steps (1) identification of the domain, (2) item generation, (3) content validity, and (4) field pre-testing of the items of the CSSUS. Furthermore, findings of Study 1 based on scale development (extraction of factors) and scale evaluation (tests of dimensionality, validity, and reliability) indicated that the CSSUS has good psychometric properties. Exploratory factor analysis (EFA) performed on sample 1 indicated a four-factor structure of the CSSUS with eigenvalues greater than one. Four factor retention criteria were employed. Three criteria indicated a four-factor structure of the CSSUS. However, one criterion indicated a two-factor structure, which was also tested. Results indicated that as compared to the two factors, the four factors could be better interpreted because they presented a psychologically meaningful solution having greater conceptual clarity. The four factors were named as justice and positivity, wisdom and excellence, courage and cautiousness, and knowledge and purposefulness. Next, confirmatory factor analysis (CFA) was performed on sample 2 to test the two- and four-factor structures of the CSSUS obtained through EFA. CFA also tested a unidimensional model of the CSSUS to examine whether the character/academic strengths construct was best explained by a single underlying factor or multiple distinct factors. Results revealed that as compared to the one- and two-factor structures, the four-factor structure had the best fit. Tests of validity and reliability were also performed on sample 2. The CSSUS and its subscales demonstrated good concurrent validity as each was significantly positively correlated with the Personal Growth Initiative Scale and Brief Perceived Social Support Questionnaire. The CSSUS and its subscales also showed adequate convergent validity as each was significantly positively correlated with the Brief Strengths Scale and its subscales. Further, the CSSUS and its subscales demonstrated appropriate discriminant validity because each was not significantly correlated with the Academic Anxiety Scale. The CSSUS and its subscales also showed adequate internal consistency reliability and the CSSUS strong split-half reliability. Moreover, based on sample 1, character virtues added unique variance in the prediction of career adaptability above and beyond the variance accounted for by gender, age, and personality traits. This indicated incremental validity of the CSSUS. Additionally, findings of Study 2—based on sample 3 indicated that three virtues (justice and positivity, wisdom and excellence, and knowledge and purposefulness) out of the four moderated the relationship between academic stress and academic thriving. Also, three virtues (wisdom and excellence, courage and cautiousness, and knowledge and purposefulness) out of the four mediated the relationship between prosocial behavior and academic engagement. The two strengths-based applications provide additional evidence of the construct and predictive validity of the CSSUS. Overall, researchers in Pakistan and abroad may use the psychometrically sound CSSUS to add greater specificity to results pertinent for furthering academic development, student learning, and career readiness.